Relevansi sistem etika Pancasila dan nilai ulul albab dalam menghadapi krisis moral generasi digital - Widad, Ziadatul (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has had a huge impact on the behavior and mindset of the younger generation. Unlimited access to information and the influx of foreign cultures through social media have a strong influence on the formation of digital character, which in many cases is not balanced with the ability to choose, filter, and control oneself. As a result, various forms of moral crises have emerged, such as the spread of hoaxes, cyberbullying, intolerance, consumptive behavior, instant culture, and the weakening of manners and social responsibility. This study aims to analyze the relevance of the Pancasila ethical system and Ulul Albab values as an ethical foundation in overcoming this moral degradation. Pancasila ethics, with its five principles, provides a moral direction that strengthens the values of divinity, humanity, unity, democracy, and social justice as guidelines for the wise use of technology. Meanwhile, the values of Ulul Albab in the Qur'an emphasize the importance of harmonizing reason and spirituality through tafakkur, tadzakkur, taqwa, amal shaleh, and dzikir as principles for forming a critical, integrity-based character that is capable of filtering information. The integration of these two concepts produces a comprehensive ethical framework for building a digital generation that is not only intellectually intelligent, but also morally and spiritually strong. The results of the study show that strengthening the values of Pancasila and Ulul Albab is very necessary in education, family, and society to create a digital generation that is moral, responsible, and able to utilize technology as a means of goodness and progress for the nation.